2016
DOI: 10.1038/ncomms12248
|View full text |Cite
|
Sign up to set email alerts
|

A single-molecule view of transcription reveals convoys of RNA polymerases and multi-scale bursting

Abstract: Live-cell imaging has revealed unexpected features of gene expression. Here using improved single-molecule RNA microscopy, we show that synthesis of HIV-1 RNA is achieved by groups of closely spaced polymerases, termed convoys, as opposed to single isolated enzymes. Convoys arise by a Mediator-dependent reinitiation mechanism, which generates a transient but rapid succession of polymerases initiating and escaping the promoter. During elongation, polymerases are spaced by few hundred nucleotides, and physical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

40
376
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(421 citation statements)
references
References 63 publications
40
376
2
3
Order By: Relevance
“…Consistent with our data, yeast TBP occupies the HSC82 heat shock promoter for 60 s in vivo (58). In human tissue culture cells, RNA polymerase II loads onto promoters approximately every 4 to 9 s to form convoys on an active gene (23). These bursts of RNA polymerase II convoys last for approximately 100 s before the promoter becomes inactive again (23).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Consistent with our data, yeast TBP occupies the HSC82 heat shock promoter for 60 s in vivo (58). In human tissue culture cells, RNA polymerase II loads onto promoters approximately every 4 to 9 s to form convoys on an active gene (23). These bursts of RNA polymerase II convoys last for approximately 100 s before the promoter becomes inactive again (23).…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the duration of RNA polymerase II convoys on the mutant TATA promoter is only slightly less than that on a wild-type TATA template (ϳ60 to 80 s) (23). Our study also revealed infrequent p53-mediated binding of TFIID on our mutant core promoter DNA lasting for a significantly long time (ϳ64 s) (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations